Comparison between piezoelectric and capacitive sensors for PD detection and signal monitoring in palm oil - Hameed, Ahmed Majid (2014)
High-voltage transformer is the most critical and expensive component in a power system network in order to ensure the stability of the system. Partial discharge (PD) detection is a technique widely used for high voltage equipment insulation condition monitoring and assessment. PD phenomenon causes gradual deterioration of the insulating materials, sometimes over a period of several years, leading perhaps to eventual failure. Detecting PD in power transformers is vital both in industries and utilities to avoid damage of high-voltage equipment. The objectives for this thesis are: To detect and analysis the PD activity using acoustic sensor (piezoelectric sensor) and capacitive sensor in natural palm-oil and to compare the sensitivity of the two sensors. The capacitive sensor and PZT sensors were immersed in palm oil tank fitted with two steel electrodes which were connected to range of high voltage (0-15KV) from high voltage source, the detecting signal that gained by the acoustic and electric sensors would pass through high pass filter to eliminate the noise range below 100-KHz then it is connected to the oscilloscope by wiring connections means. These data will evaluate in time and frequency domain by using analyzing software program (Origin-Pro). The conclusion that can acquire from this software and from the experimental lap results shown impressive characteristic for the PD detection and recommend the both sensors as a good tools for monitor and assessment the insulation condition when the discharge emission occur.